Kesejahteraan Siswa Di Sekolah Berasrama - Kurniasih, Nursita, Dr. Sri Lestari, M.Si s (2017)
The purpose of this study was to describe the students well-being in boarding schools. This study used a qualitative phenomenology approach referring to six junior high school students in one of the Islamic Boarding School in Surakarta as main resources. Interview techniques method is used to collect required data, while the credibility / validity of those data using triangulation of data sources. The results of this research showed that; Students at boarding school initially experience low wellbeing characterized by the appearance of sadness, want to go home soon, they like to be alone because of friends bullying, but with the passage of time students can adapt properly because they became more familiar with friends, closer to the dormitories teachers, having many pleasing activities, so that their wellbeing increasing, as evidenced by the fulfillment of the following aspects: (1) loving (social-emotional relationships), (2) being (means for self-fulfilment), (3) having (school conditions), and (4) health (health status). Supporting factors to ensure the students wellbeing in boarding schools are: (1) A proper school management (2) social support (3) self development opportunity. While the factors that hamper the students wellbeing in boarding schools are: (1) the cleanliness of the school environment is not maintained, (2) teachers change/turn over, (3) conflict with friends, (4) yearn for parents (5) negative self-concepts. Other findings from this research are many spiritual things that arise like a sense of gratitude that makes students feel prosperous, safe, comfortable, i.e. through the islamic learning system in the boarding school that makes students motivated to learn eagerly, such as the pursuit of target memorization of al-qur'an, run practice of sunnah worship and seek knowledge of the world and the hereafter for more. Gratitude can be then leverage of students' wellbeing during the boarding school. The conclusion of this research is that the dynamics of students' wellbeing in boarding school has been fulfilled in terms of 4 aspects mentioned above. Implication of this research is for boarding schools that need to improve their students' wellbeing need to fulfill 4 aspects/criteria mentioned above. Keywords: Student Wellbeing, Boarding School Tujuan dari penelitian ini adalah untuk mendeskripsikan dinamika kesejahteraan siswa di sekolah berasrama. Penelitian ini menggunakan metode kualitatif fenomenologi dengan jumlah informan 6 siswa SMP di salah satu sekolah islam berasrama di Surakarta. Metode pengumpulan data menggunakan teknik wawancara, sedangkan keabsahan data menggunakan triangulasi sumber data. Hasil penelitian menunjukkan bahwa; Siswa di sekolah berasrama pada awalnya mengalami kesejahteraan yang rendah yang ditandai dengan munculnya rasa sedih, ingin pulang ke rumah, suka menyendiri karena dibully teman, namun dengan berjalannya waktu siswa dapat beradaptasi karena lebih akrab dengan teman, lebih dekat dengan guru pendamping asrama, banyak kegiatan yang menyenangkan, sehingga kesejahteraannya meningkat, yang terbukti dengan terpenuhinya aspek-aspek berikut: (1) loving (hubungan sosial-emosional) (2) being (pemenuhan diri), (3) having (kondisi lingkungan fisik sekolah), (4) health (kesehatan). Faktor pendukung kesejahteraan siswa di sekolah berasrama yaitu: (1) Pengelolaan sekolah yang baik (2) Dukungan Sosial (3) Kesempatan Pengembangan Diri. Sedangkan faktor penghambat kesejahteraan siswa di sekolah berasrama yaitu: (1) kebersihan lingkungan sekolah kurang terjaga, (2) terjadi pergantian guru pendamping asrama, (3) konflik dengan teman, (4) merindukan orangtua, (5) konsep diri yang negatif. Temuan lain dari penelitian ini adalah banyak hal-hal spiritual yang muncul seperti rasa kebersyukuran yang membuat siswa merasa sejahtera, aman, nyaman, yaitu melalui sistem pembelajaran islami di asrama yang membuat siswa termotivasi belajar, seperti mengejar target hafalan al-qur'an, menjalankan amalan ibadah-ibadah sunnah dan mencari ilmu dunia dan akhirat. Rasa syukur tersebut dapat menjadi daya ungkit kesejahteraan siswa selama di asrama. Kesimpulan dari penelitian ini adalah bahwa dinamika kesejahteraan siswa di sekolah berasrama sudah terpenuhi ditinjau dari 4 aspek tersebut di atas. Implikasi dari penelitian adalah bagi sekolah-sekolah berasrama apabila ingin meningkatkan kesejahteraan siswanya maka perlu memenuhi 4 aspek/kriteria tersebut diatas. Kata Kunci: Kesejahteraan Siswa, Sekolah Berasrama